Robert Knight : reforming editor in Victorian India - Hirschmann, Edwin, 1932- (Oxford ; New York : Oxford University Press, 2008)
Historical biography of Robert Knight, 1825-1890, founder and first editor of Times of India, Mumbai and Statesman, Kolkata.
Includes bibliographical references (p. [249]-262) and index.
Keywords: Knight, Robert, -- 1826-1890.; Times of India (Firm) -- History; Newspaper editors -- Great Britain -- Biography; Newspaper editors -- India -- Biography; Newspaper publishing -- India -- History -- 19th century; Newspapers -- History -- 19th century; India -- History -- 19th century